2010
DOI: 10.1002/cbdv.200900009
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Polyprenylated Acylphloroglucinols and Chromone O‐Glucosides from Hypericum henryi subsp. uraloides

Abstract: Two new C(30)-epimeric polycyclic polyprenylated acylphloroglucinols (PPAPs), named uralodins B and C (1 and 2, resp.), were isolated from the aerial parts of Hypericum henryi subsp. uraloides together with two new chromone glucosides, urachromones A and B (3 and 4, resp.), as well as 16 known compounds. Their structures were established by extensive NMR techniques and MS analysis. The epimers 1 and 2 always behaved like a single compound when examined by TLC, and were separated by HPLC. Their configuration wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Distributed in 30 genera, the plants of the Clusiaceae family include economically relevant trees, shrubs, lianas and herbs used in the production of edible fruit, hardwood and chemical derivatives with interesting pharmacological and industrial properties . More specifically, the plants of the Platonia genus are rich in natural products with relevant biological activities , such as antimicrobial , leishmanicidal , antidepressant , cytotoxic , anti‐HIV , anti‐inflammatory , anticonvulsant and antitumour effects.…”
mentioning
confidence: 99%
“…Distributed in 30 genera, the plants of the Clusiaceae family include economically relevant trees, shrubs, lianas and herbs used in the production of edible fruit, hardwood and chemical derivatives with interesting pharmacological and industrial properties . More specifically, the plants of the Platonia genus are rich in natural products with relevant biological activities , such as antimicrobial , leishmanicidal , antidepressant , cytotoxic , anti‐HIV , anti‐inflammatory , anticonvulsant and antitumour effects.…”
mentioning
confidence: 99%
“…Besides 15 signals for three prenyl groups, 13 C NMR spectrum showed signals for three methylene and four quaternary carbons including signals for two nonconjugated carbonyl groups at d 208.2 and 207.9 and two methine signals. In addition, the key HMBC correlations (Figure 2) of H-4 with C-3, C-5, C-6, and C-2, H-5 with C-1, C-4, C-6, and C-20, H-8 with C-9, C-7, and C-6, and H-7 with C-1, C-6, and C-9 verified the core bicyclo[3.3.1]nonane-1,9-dione system [11,12]. HREIMS required the compound to be bicyclic, considering the subtraction of five double bond equivalents for two carbonyl groups and three prenyl double bonds.…”
Section: Resultsmentioning
confidence: 93%
“…The above ROESY peaks indicated that 1 had the same relative configuration at C-2, C-3, and C-6 as furohyperforin and uralodin B [12]. Hence, the structure of 1 was elucidated and named as dorstenpictanone (1).…”
Section: Resultsmentioning
confidence: 96%
“…Fraction B was subjected to a series of chromatographic methods, and led to the isolation of four new acylphloroglucinol derivatives, hypercohones D–G ( 1 – 4 ), together with four known ones, uralodin A ( 5 ), [17] uralodin B ( 6 ), [18] oxepahyperforin ( 7 ) [19], and tomoeone E ( 8 ) [20]. …”
Section: Resultsmentioning
confidence: 99%